Warriors. The rise of Scourge - Hunter, Erin; Jolley, Dan (Hunter, Erin. Warriors (Graphic novel), 2024)
When kittypet Tiny crosses paths with some wild forest cats defending their territory, they leave him with scars -- and a bitter, deep-seated grudge. As his reputation grows among the strays and loners that live in the dirty brick alleyways of Twolegplace, he changes his name to Scourge and puts everything about his old life behind him... except his deadly desire for revenge.